## Trending News

# Find k ................................?

-k^3+k^2+2*k+4

I need to calculate k from this equation.

Update:

its equal to 0

### 1 Answer

Relevance

- Mr. RizLv 69 years agoFavorite Answer
-k^3 + k^2 + 2*k + 4

= -k(k^2 -k - 2) + 4

= -k(k^2 -2k + k -2) + 4

= -k[k(k-2) + 1(k-2)] + 4

= -k(k+1)(k-2) + 4

How do you want us to calculate? What is the expression equal to???

It's not an equation to solve for k.

===========================

AFTER THE EDIT:

-k(k+1)(k-2) + 4 = 0

-k(k+1)(k-2) = -4

k(k+1)(k-2)= 4

k = 4/(k+1)(k-2)

- Login to reply the answers

Still have questions? Get your answers by asking now.